From Dostoevsky to Stevenson: on the Social-Psychologic Diagnoses and Prognoses in the Works of the Writers - Gonchar-Khanjyan, Natalya (Bulletin of Yerevan University H: Russian Philology, 2022)
The ideological, moral, and psychological problems, motives, and characters of F. Dostoevsky’s prose went well beyond national literature during his lifetime. F. Dostoevsky’s prose had a particular impact on R. L. Stevenson, who, after Dostoevsky, raised the issues of the contemporary world (suicide and the soul, dualism, split personality, multiple personality disorder, etc.) in his works and suggested keys to their resolution. The article presents a number of observations on two topics (duality and suicide), bringing Stevenson closer to Dostoevsky. The writers’ versions of both themes are examined in connection with the sphere of interests and studies in contemporary psychology.